The emergence of digital transformation in the automotive industry - Industry 4.0 in Hungary - Tóth-Kaszás, Nikoletta; Ernszt, Ildikó; Péter, Erzsébet; Mihalics, Bálint (Competitio, 2022)
It is no exaggeration to say that the digital transformation can be seen as both a paradigm shifts and a real technological revolution (Perez, 2010, Mergel, et al., 2019). In order to get to know the preparedness of the Hungarian automotive industry players in the topic, we conducted an empirical research in October - December 2020. The main goal was to determine the level of automotive actors in the digital transformation process. Company leaders were primarily asked about their progress in the digital transition process, its opportunities and challenges, organizational culture, and potential human resource management responses. This study focuses on the digital transition concentrating on the following dimensions: strategy and leadership, human resources, business processes, supply chain, manufacturing, products and services. Based on the results, we classified the examined Hungarian automotive industry actors into clusters.